SELF-ESTEEM OF HIGHER SECONDARY STUDENTS : A STUDY IN KAMRUP DISTRICT - Dr. Pallabi Mali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of the present study was to study the self-esteem of Higher Secondary students. The study was conducted on a sample of 600 Higher Secondary students studying in Govt., private and provincialized schools/colleges from arts, science and commerce stream of Kamrup district. Self-esteem Inventory prepared by M.S Prasad and G.P Thakur was used to collect data. Normative survey method was used to collect data. The study indicate that most of the H.S students have lack of knowledge on the concept of Self-esteem